UPAYA MENINGKATKAN KETERAMPILAN MENULIS SURAT DINAS DENGAN PENDEKATAN KONTEKSTUAL PEMODELAN SISWA KELAS VIII A SMP NEGERI 2 PIYUNGAN, BANTUL - Suprapto Suprapto (Universitas Sarjanawiyata Tamansiswa, 2018)
This study was a classroom action research by following a cycle model in which each cycle consists of four stages of activity. The aim of study was to improve the writing competence of the official letter at class VIII A Junior High School 2 Piyungan Bantul in first semester of 2016/2017 through the application of Contextual Approach Modeling. The object of study was the basic competence of writing official letter number 4.2 in class VIII first semester. The method of data collections were tests, classroom observations, classroom field notes, and questionnaires. After Contextual Approach Modeling was applied in the process of writing official letter dan the learning of process quality. The learning of process quality increased was marked by the increasing students activity in the learning process. The cycle I, the students activity were 23 children (82%) and the cycle II, the students activity were increased to 25 children (89%). Then, the improvement outcomes of learning process was marked by the increasing of average value in the writing test of official letter from 81.3 to 82.5. The achievement of learning process was decreased from 85.7% to 80.8%.